The Influence of Self Concept, Autonomy Education, Creativity and Students’ Creativity Towards Result Learn Physics - Umayya Ulfah (Wacana Journal of Social and Humanity Studies, 2020)
Self-concept and autonomy education are two internal factors that give students the strength of mind so that it can encourage students’ learning process, achievement, initiative, and creativity. This research aims to investigate whether or not there is a direct or an indirect effect of self-concept, autonomy education, and creativity on student’s physics study results. The method used was survey with a sample of 190 students spread across six senior high schools in the Tuban Regency, namely SMAN 1 Jatirogo, SMAN Parengan, SMAN Bangilan, SMAN 1 Tuban, MA Assalam and MAN Rengel with stratified random sampling techniques. The data analysis technique used is the path analysis technique. The result shows that: (1) There are 29.2 % of direct influence of self-concept towards student’s physics study result, 13.8% of indirect influence of creativity, and 10.6% of autonomy education; (2) There are 17.1 % of direct influence of autonomy education towards result learn the physics,  and 10.9 % of indirect influence through creativity; (3)  The influence of self-concept towards creativity indirectly are  41.2% and indirectly through autonomy education are 19.9%; (4) There are 33.5% of direct influence of creativity towards student’s physics study result; (5) The direct influence of autonomy educations towards creativity are 32.2%; and (6) There are 62% of direct influence of self-concept towards autonomy education.